Pemberdayaan ekonomi kelompok nelayan Desa Pangkah Kulon-Gresik dalam memproduksi kerupuk ikan sebagai upaya peningkatan nilai ekonomi ikan sortiran - Muhammad Faisal Ibrahim; Ngatini Ngatini (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Pangkah Kulon is one of the villages in Gresik Regency which is located in Ujung Pangkah District, Gresik, East Java. The lack of public knowledge about fish processing makes people required to be more creative in increasing the selling value of fish into processed products. So far, fresh fish caught by fishermen are sold directly to middlemen, while fresh fish that do not pass the sorting is simply thrown away. To increase the economic value of fish into high selling value products, training in the production of fish crackers is carried out. The training was conducted on the socialization of creative preparations, training on the manufacture and creative industry of fish crackers. In this training, participants (fishermen's wives) are trained to operate production equipment, from dough making, milling, to cutting. The knowledge and skills provided can be used as a pioneering effort for the fish cracker creative industry which is a favorite food for the community in general. In addition, it is also a business opportunity that can increase household income.